Hermeneutics on Hadith; Study on Muhammad Iqbal Thought - Nur Khasanah; Achmad Irwan Hamzani; Havis Aravik (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
AbstractThis study discussed the thoughts of Muhammad Iqbal about the study of hermeneutics in hadith. The study aimed to find out how Muhammad Iqbal's thought about the study of hermeneutics in hadith. The study is a qualitative study based on the library (library research). The approach used is descriptive qualitative which aimed to illustrate or describe the reality that exists or what is happening or the actual reality of the object under the study. The result of this study showed that Muhammad Iqbal's thought about hermeneutics studies in a hadith is Muhammad Iqbal's thought in the hadith which was originated on an assumption that hadith as a second source that did not miss the contradictions of the people both the truth of the content (matan) and the chain of transmission (sanad) and it became wild critiques by the orientalists from the past time till now on. Iqbal suggested that an in-depth study of the hadith literature by directing the Prophet Muhammad himself as a person who has the authority to interpret his revelations. it is all because the Prophet was the one who knew the true purpose of the message conveyed by Allah SWT well.Keywords: Muhammad Iqbal, Hermeneutika, Hadith AbstrakStudi ini membahas pemikiran Muhammad Iqbal tentang studi hermeneutika dalam hadits. Penelitian ini bertujuan untuk mengetahui bagaimana pemikiran Muhammad Iqbal tentang studi hermeneutika dalam hadits. Penelitian ini adalah penelitian kualitatif berdasarkan perpustakaan (library research). Pendekatan yang digunakan adalah deskriptif kualitatif yang bertujuan untuk menggambarkan atau menggambarkan kenyataan yang ada atau apa yang sedang terjadi atau kenyataan aktual dari objek yang diteliti. Hasil penelitian ini menunjukkan bahwa pemikiran Muhammad Iqbal tentang studi hermeneutika dalam sebuah hadis adalah pemikiran Muhammad Iqbal dalam hadits yang berawal dari asumsi bahwa hadits sebagai sumber kedua yang tidak ketinggalan kontradiksi masyarakat, baik kebenaran dari konten (Matan) dan rantai penularan (sanad), dan itu menjadi kritik liar oleh orientalis dari masa lalu sampai sekarang. Iqbal menyarankan agar penelitian mendalam tentang literatur hadits dengan mengarahkan Nabi Muhammad sendiri sebagai orang yang memiliki wewenang untuk menafsirkan wahyu-wahyunya. Itu semua karena Nabi adalah orang yang mengetahui tujuan sebenarnya dari pesan yang disampaikan oleh Allah SWT dengan baik.Kata Kunci: Muhammad Iqbal, Hermeneutika, Hadits